(untitled) (Economics and region, 2020)
The requirements for domestic industrial enterprises in the conditions of globalization of the world markets are outlined, the directions of transformational changes are formulated and the prerequisites for transformation of communication business processes of industrial enterprises are systematized. The authors’ conceptual model of implementation of digital transformations in the communication business processes of industrial enterprises is proposed, which includes the following blocks: 1) determinants and basic foundations of conceptual changes; 2) potential of the enterprise for internal digitization of business; 3) a practical toolkit for the implementation of digital transformations in the communication business processes of industrial enterprises.